Biomechanics of Muay Thai : science behind the low kick - Zeng, Ezra Yueyi (2019)
The low kick is a popular technique used by Muay Thai fighters to achieve many different outcomes and advantages. The main motions involved in the execution of the low kick is the 3-dimensional rotations of the leg segments and the body. In Muay Thai, little attention is given to the kinematic, kinetic and the dynamic concepts and principles involved that form the techniques that are now used today. Most studies involving Muay Thai focus on nutrition, medical and psychological studies. There are some studies that have attempted to investigate characteristics of Muay Thai kicks by use of accelerometers and force pressure plate to record kick data. However, the exclusion of mechanical methods persists in current literature and hence actual understanding of the science behind the Muay Thai from an engineer’s perspective is still missing. This project applies the principal laws and concepts from kinematics, kinetics and dynamics in order to theoretically find out how kicking angle and kicking height affects the change in displacement of the target’s overall centre of gravity. It was found that the lower the kick, the higher the kick force from the user and between the defined angles 120° to 240° about the projected vertical of the target’s leg is most likely to unbalance the target, assuming the target’s leg is rigid and the target is static while standing up.